An international serum standard for application in assays to detect human complement activation products - Bergseth, Grethe; Ludviksen, Judith K.; Kirschfink, Michael; Giclas, Patricia C.; Nilsson, Bo; Mollnes, Tom E. (Molecular immunology, 2013)
The importance of the complement system in clinical medicine has become evident during the last decades and complement therapeutics has now reached the clinic. Thus, there is an increased interest in and need for assays to evaluate complement activity and dysfunction. Pathologically increased complement activation can indirectly be evaluated by quantification of complement components, but in order to exactly measure such activation, assays for quantification of products formed during activation are required. Progress in this field is hampered by lack of standardization. Therefore, members of the International Complement Standardization Committee, a joint initiative of the International Complement Society and the International Union of Immunological Societies (IUIS), prepared a defined standard for application in assays for complement activation products. We here report on the production and properties of this International Complement Standard #2 (ICS#2). ICS#2 was made from a pool of sera from healthy blood donors (ICS#1) that was activated with a combination of heat-aggregated IgG and zymosan, and subsequently stabilized by adding EDTA and nafamostat mesylate. The protocol was optimized to make the standard applicable in the following activation product assays: C1rs-C1-inhibitor complexes, C4a, C4bc, C4d, Bb, C3bBbP, C3a, C3bc, C3dg, C5a and the soluble terminal C5b-9 complement complex (SC5b-9, TCC). ICS#2 was defined as containing 1000 complement activation units (CAU)/mL for all activation products measured. All activation products were stable after 10 times thawing and freezing and most of the activation products were stable during storage at 4°C for up to 21 days. ICS#2 was produced large-scale and is considered a valuable tool for standardization, calibration and reference control for complement activation assays, providing the necessary prerequisite for quality assessments between complement laboratories.